Delinquent by Reason of Poverty - Tamar R. Birckhead (Washington University Journal of Law & Policy, 2012)
This Article, written for the 12th Annual Access to Equal Justice Colloquium, explores the disproportionate representation of low-income children in the U.S. juvenile justice system. It examines the structural and institutional causes of this development, beginning with the most common points of entry into delinquency court—the child welfare system, public schools, retail stores, and neighborhood police presence. It introduces the concept of needs-based delinquency, a theory that challenges basic presuppositions about the method by which children are adjudicated delinquent. It argues that at each stage of the process—from intake through adjudication to disposition and probation—the court gives as much or more weight to the perceived "needs" of the child and her family than to the quality of the evidence against her or the ability of the state to prove its case. Typical features of the juvenile code, including the procedures for intake and diversion and the use of bench rather than jury trials, combine to shift the system's emphasis from an evaluation of a child's criminal responsibility to an assessment of a family's social service needs. The standard of proof, therefore, is determined in large part by the socioeconomic class of the accused rather than the nature of the forum, an orientation that lowers the state's burden for indigent juveniles while heightening it for affluent youth. The result is that in all but the most serious of cases, children from low-income homes do not have to be as "guilty" as those from families of means in order to enter and remain in the system, thereby widening the net of court intervention for poor children. The Article establishes that the juvenile court‘s traditional focus on the needs of destitute youth continues to be reflected in the system‘s practices and procedures, despite the modern court‘s shift in dispositional philosophy from rehabilitation to youth accountability and public safety. It argues that the emphasis on families‘ needs when adjudicating delinquency has a disproportionate effect on low-income children, resulting in high rates of recidivism and perpetuates negative stereotypes based on class. It offers strategies for confronting and reversing this trend, including data collection that records the income-level of juveniles‘ parents; initiatives that raise awareness of needs-based delinquency among police, prosecutors, defenders, judges, and agency personnel; diversion programs that reduce the high rate of juvenile court adjudications for minor offenses; cross-agency mental health treatment plans for children and adolescents; and the adoption of international juvenile justice models that are preventative and diversionary rather than penal and punitive. The Article challenges the view that in tight budgetary times, court involvement is the only way for poor children to access services. It concludes by calling for lawmakers and system players to end the practice of needs-based delinquency, with the goal of increasing fairness for all youth in the juvenile justice system.
Keywords: In re Gault; 387 U.S. 1 (1967); Children' s legal assistance; Juvenile delinquency; Poor children; Right to counsel; United States